Temporal expression of a putative homogentisate solanesyltransferase cDNA in wounded Aquilaria malaccensis, an endangered tropical tree - Anor Basah, Azzarina; Mohamed, Rozi; Siah, Chai Har; Wong, Mun Theng (Universiti Putra Malaysia Press, 2017)
Homogentisate prenytransferase (HPI) generally catalyses prenylation reactions in tocochromanol and plastoquinone-9 biosynthesis, while homogentisate solanesyltransferase (HST) is specific to reaction leading to plastoquinone, an essential component in the synthesis of carotenoid, a powerful antioxidant and precursor to vitamin A. In Aquilaria spp. abiotic stress in the form of wounding is the main trigger for the production of a highly-valued terpene-rich wood known as agarwood. Putative HST cDNA, AmHST1 was cloned from total RNA of callus tissue of Aquilaria malaccensis using reverse transcription approach. Based on a partial HST sequence, specific primers were initially designed to amplify the internal open reading frame region followed by RACE, which successfully amplified the cDNA. The partial length AmHST1 cDNA measured about 1182 bp nucleotides and encodes a polypeptide of 392 amino acid. Sequence alignment revealed that AmHST1 shares 74% - 77% similarity with HPT from Arabidopsis and Theobroma cacao. Gene expression analysis indicated that the AmHST1 expression was suppressed in wounded tissues. Results suggest that there should be a potential trade-off between genes involved in plastoquinone and terpenoid synthesis as they both share similar upstream genes and precursors. When facing a major abiotic stress such as wounding, the latter is favoured.